Reliability and validity of a short questionnaire to measure authoritarian attitudes in adolescents - Carrión María, María Carmen; López Espín, José Juan; Gascón Cánovas, Juan José; Torres Cantero, Alberto Manuel (Anales de Psicología / Annals of Psychology, 2012)
Objective: Design and validate a short measurement scale of authoritarianism for teenagers. Methods: The items and dimensions were formulated to adapt the concepts related to authoritarian attitude (set of beliefs and feelings that induce to discriminate and exercise violence on those subjects that are perceived as different) to the specific context of adolescence. Initially, 14 items corresponding to the most habitual attitudes of authoritarian type in the teen period (gender tolerance, ethnic diversity tolerance and scholar violence attitudes) were identified. The questionnaire was provided to a sample of 1960 pupils belonging to Secondary Education Schools. Results: In the factorial analyses, 3 out of the 14 initial items were eliminated. The three dimensional model proposed here showed good adjustment (GFI= .96) and achieved high consistency (alpha of Cronbach= .83) confirming its construct validity.